Defining Efficacy of Chikungunya Virus Candidate Vaccines: Different Endpoints Derived From the Virus—Cytokine—Ferritin (VCF) Model - Lim, Stephanie M.; Dutta, Sudip K.; Martina, Byron E. E. (Frontiers in Virology, 2021)
Following the disruptive epidemics throughout the Indian Ocean, Southeast Asia and the Americas, efforts have been deployed to develop an effective vaccine against chikungunya virus (CHIKV). The continuous threat of CHIKV (re-)emergence and the huge public health and economic impact of the epidemics, makes the development of a safe and effective vaccine a priority. Several platforms have been used to develop candidate vaccines, but there is no consensus about how to translate results from preclinical models to predict efficacy in humans. This paper outlines a concept of what constitutes an effective vaccine against CHIKV, which may be applied to other viral vaccines as well. Defining endpoints for an effective vaccine is dependent on a proper understanding of the pathogenesis and immune response triggered during infection. The preclinical model adopted to evaluate experimental vaccines is imperative for the translation of preclinical efficacy data to humans. Several CHIKV animal models exist; however, not all provide suitable endpoints for measuring vaccine efficacy. This review summarizes the current knowledge related to CHIKV pathogenesis and the correlates of protection. We then define what would constitute an effective CHIKV vaccine in humans using four key endpoints, namely: (i) prevention of chronic disease, (ii) prevention of acute disease, (iii) prevention of transmission to mosquitoes, and (iv) complete prevention of infection. Lastly, we address some of the gaps that prevent translation of immunogenicity and efficacy findings from preclinical models to humans, and we propose to use the combination of virus–cytokine–ferritin levels as a read-out for measuring vaccine-induced protection.